The concept structure of student in mathematical literacy - Hadi Sopandi; Supratman; Sinta Verawati Dewi (Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2024)
Mathematical literacy is crucial for students to apply mathematical concepts in real-world contexts. This study investigated the structure of students' concepts in mathematical literacy, focusing on a case study of a single eighth-grade student (S11) at SMP Negeri 9 Kota Tasikmalaya, Indonesia. Using a qualitative exploratory approach, the research employed a modified PISA mathematical literacy test, followed by a semi-structured interview and analysis of the student's work. Data analysis followed the interactive model proposed by Miles and Huberman which involved three concurrent flows of activity namely data reduction, presentation and conclusion drawing. The results revealed that S11 only met the assumption indicator of mathematical literacy, leading to an incomplete and inaccurate conceptual structure. The study identified multiple instances of concept structure fragmentation, specifically hole construction fragmentation and pseudo-construction fragmentation. These fragmentations were attributed to limited reading comprehension skills, incomplete recording of question information, failures in mathematical concept construction (particularly in division), difficulties in assimilating and accommodating new information, and lack of social interaction with more competent individuals. These results provide valuable insights into students' challenges in applying mathematical concepts to practical scenarios.